Genesis and Evolution of NASA’s Satellite Ocean Color Program - McClain, Charles R.; Franz, Bryan A.; Werdell, P. Jeremy (Frontiers in Remote Sensing, 2022)
We recount, based on our involvements in NASA ocean color flight projects, the chronology of technical challenges, lessons learned, and key developments over the past 40+ years of NASA satellite ocean color, beginning with the Nimbus-7/Coastal Zone Color Scanner, that have led to the upcoming Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) mission. Topics include the evolution of (1) satellite ocean color and field bio-optical data access, (2) satellite sensor capabilities, i.e., CZCS to PACE’s hyperspectral Ocean Color Imager, OCI, (3) atmospheric corrections, (4) pre- and post-launch sensor characterization and calibration, (5) bio-optical algorithms, (6) in situ-derived radiometry and photosynthetic pigment data measurement quality, and (7) applications of hyperspectral satellite observations.